Comparative Study of Outcomes in Stroke Patients Receiving TPA within 3 vs. 4.5 Hours of Symptom Onset - Dr. Suhas Sopan Borole; Dr. Shaunak Ramakant Patil; Dr. Nitesh Suresh Chhajed (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Timely administration of tissue plasminogen activator (tPA) is crucial for effective stroke management, but the optimal therapeutic window remains under debate. This study examines the outcomes of stroke patients treated with tPA within two distinct time frames: within 3 hours and between 3 to 4.5 hours of symptom onset. Methods: In this retrospective cohort study, 180 stroke patients (90 in each group) treated at a tertiary care center were analyzed. Patients receiving tPA within 3 hours of onset were compared with those treated within 4.5 hours regarding functional outcomes, complication rates, and long-term disability and mortality. Functional independence, neurological improvement, and incidence of complications such as intracerebral hemorrhage were assessed. Statistical significance was determined using chi-square and t-tests, with a p-value <0.05 considered significant. Results: Patients treated within 3 hours showed a higher rate of functional independence at 3 months (54% vs. 47%, p=0.29) and better improvement in NIHSS scores. The incidence of intracerebral hemorrhage was lower in the 3-hour group (6.7% vs. 13.3%, p=0.05). Moreover, earlier treatment was associated with lower rates of severe disability and mortality at 6 months, although these differences did not reach statistical significance. Conclusion: This study suggests that treating stroke patients with tPA within 3 hours of symptom onset may lead to better functional outcomes and fewer complications compared to treatment within 4.5 hours. Despite the non-significant differences in some outcomes, the findings support the current clinical emphasis on the earliest possible administration of tPA.